Incidence of Fusarium in certain food grains - S. GIRISHAM and S.M. REDDY, K. NARASIMHA RAO*, B. VIJAYAPAL REDDY (Indian Phytopathology, 2008)
Incidence of Fusarium in pre- and post-harvest samples of sorghum, maize, paddy and pulses was analysed and their mycotoxingenic potential was determined in all species of Fusarium. F. moniliforme was more dominant and occurred in the spermosphere of all the seed samples. Significant percentage of strains were mycotoxigenic and produced one or other mycotoxin. Fumonisins, T-2, zearalenone, DON, neosolaneol and nivalenol were some of the mycotoxins recorded.